TEORI KONFLIK DAN KEKERASAN JOHAN GALTUNG: STUDI NETNOGRAFI DALAM KOLOM MEDIA BANDUNGBERGERAK.ID - Manuella Princessa; Gabriel Putra Pratama; Grace Derio; Yutaro Yoshikoshi; Fajar Fatrias Akbar; Mochamad Ziaul Haq (Integritas Terbuka: Peace and Interfaith Studies, 2026)
This study aims to analyze the representation of conflict and social violence in the alternative media coverage of BandungBergerak.id using Johan Galtung’s ABC Triangle theory. This study is important because social conflict in urban society does not only appear in the form of physical violence, but also operates through structural and cultural violence that often remains invisible in everyday life. This study employed a qualitative research design using a virtual ethnography approach. The researcher selected the virtual ethnography method because the study focused on social activities and conflict representations that developed within digital spaces. The research data originated from the documentation of BandungBergerak.id news articles discussing bullying, restrictions on religious worship, femicide, forced evictions, and environmental conflicts. The researcher then analyzed the data using narrative analysis techniques through Johan Galtung’s ABC Triangle theoretical framework. The findings show that social conflict in BandungBergerak.id coverage does not only represent direct violence such as intimidation, bullying, femicide, and forced evictions, but also reveals structural violence through discriminatory policies, social marginalization, and weak state protection toward vulnerable groups. In addition, this study found cultural violence operating through patriarchy, intolerance, social stigma, and discriminatory language that normalize inequality within society. The findings also demonstrate that BandungBergerak.id presents narratives of conflict transformation through social empathy, community solidarity, environmental movements, and nonviolent practices based on constructive journalism. This study contributes to the development of Johan Galtung’s conflict studies by expanding the analysis of the relationship between digital media, structural violence, and conflict transformation in contemporary urban society. The originality of this study lies in its use of a virtual ethnography approach and the ABC Triangle theory to examine local alternative media as both a space for conflict representation and an arena for peace transformation.